Correction: Magnetic control of cellular processes using biofunctional nanoparticles. Issue 12 (1st November 2017) - Monzel, Cornelia; Vicario, Chiara; Piehler, Jacob; Coppey, Mathieu; Dahan, Maxime
Abstract : Correction for 'Magnetic control of cellular processes using biofunctional nanoparticles' by Cornelia Monzel et al., Chem. Sci., 2017, 8, 7330–7338.